2022
DOI: 10.3390/biomedicines10061278
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells in Osteoarthritis: Evidence for Structural Benefit and Cartilage Repair

Abstract: Osteoarthritis (OA) presents a major clinical challenge to rheumatologists and orthopedists due to the lack of available drugs reducing structural degradation. Mesenchymal stromal cells (MSCs) may represent new therapeutic approaches in cartilage regeneration. In this review, we highlight the latest knowledge on the biological properties of MSC, such as their chondrogenic and immunomodulatory potential, and we give a brief overview of the effects of MSCs in preclinical and clinical studies of OA treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…In detail, EV-miRNAs had a preponderance towards protection for cartilage (ratio of 10.3), anti-inflammatory phenotype for macrophages (M2 vs. M1 ratio of 10.2) and anti-activation for T cells (ratio of 3.0). This is again consistent with the amelioration of cartilage structure and reduction in inflammation observed after MSCs or MSC-based products in OA patients [ 58 , 59 , 60 ]. In particular, two miRNAs tipped the balance towards healing capacity, hsa-miR-24-3p and hsa-miR-222-3p.…”
Section: Discussionsupporting
confidence: 84%
“…In detail, EV-miRNAs had a preponderance towards protection for cartilage (ratio of 10.3), anti-inflammatory phenotype for macrophages (M2 vs. M1 ratio of 10.2) and anti-activation for T cells (ratio of 3.0). This is again consistent with the amelioration of cartilage structure and reduction in inflammation observed after MSCs or MSC-based products in OA patients [ 58 , 59 , 60 ]. In particular, two miRNAs tipped the balance towards healing capacity, hsa-miR-24-3p and hsa-miR-222-3p.…”
Section: Discussionsupporting
confidence: 84%
“…However, it is understood that progressive degradation and other aberrant changes in the joint tissues eventuate in an inflammation-mediated feedback loop that propagates the disease. Because of their ability to produce growth factors and anti-inflammatory cytokines that support tissue repair and regeneration, 31 MSCs are considered a promising biological therapy for mitigating OA. However, as MSCs can be derived from different tissue sources, it is of significant interest to determine if a specific MSC source illustrates heightened therapeutic potential for the treatment of OA.…”
Section: Discussionmentioning
confidence: 99%
“…(5). Research over the last few years has suggested that MSCs hold great potential for diverse therapeutic applications through putative immunomodulatory, anti-inflammatory effects or by stimulating tissue regeneration (6)(7)(8)(9).…”
Section: Mesenchymal Stromal Cell-based Therapiesmentioning
confidence: 99%
“…Regarding articular diseases, MSCs have shown the potency to reduce OA-related pain and increase cartilage repair (6,9). Additionally, OA-afflicted horses treated with intra-articular injections of MSCs show improvement in clinical signs, cartilage appearance and athletic performance (10)(11)(12).…”
Section: Mesenchymal Stromal Cell-based Therapiesmentioning
confidence: 99%